Effect for two types of explant for prebasic seed production of native potato (solanum phureja luz et. buk) "yema de huevo" (2001)
Presently micropropagation techniques are used a tool forpota toe seed production which guarantees, through anadequate process, healthy seed tubers, and rapid multiplication. In the diploid potato Solanum phureja cultivar «yema de huevo» the multiplication «in vitro» was developed successfully. There fore the following step, the production of explants in greenhouse (prebasic seed), requires the studies to optimize this phase. This work was carried out establish to the density and the type of explants optimum, to develop the production of prebasic seed under greenhouse conditions. The trial was carried out following a completely randomized design, with factorial array (4x3). The first factor was the distance among plants and, the second, the type of explants. The experiment was carried out in the San Jorge Experimental Station greenhoused ofthe ICA to 2800 masl. It was found that a 6 cm distance between plants optimizes the production and a distance of 9 cm between plants, optimizes the multiplication rateo The best type of explants was the lateral steam.